Dinamika Komposisi Penduduk: Dampak Potensial Pandemi Covid-19 terhadap Demografi di Indonesia - Sari Lestari Zainal Ridho; Syaiful Aqli Yusuf (Populasi, 2020)
This study aims to observe and analyze the development of trend of COVID 19 and its potential impact on changes in population composition based on age structure in Indonesia. Using Covid-19 cases data obtained from the Ministry of Health of the Republic of Indonesia and forecasting method by comparing several models, the study findings indicate that the trend shows increasing cases and will continue to rise as long as there is no intervention. Experimentally, the mortality cases dominated by the male and elderly population are the possible causes to the change in the composition of the population based on the age structure. Hence, it is necessary to immediately intervene it in the form of policies in health sector that are more appropriate to maintain the sustainability of Indonesia’s human resources since demographic dynamics, particularly in terms of sex, age structure, and health conditions, also have a significant macroeconomic implication.